Albert Ladenburg (1842-1911) – The Distinguished German Chemist and Historian of Chemistry of the Second Half of the XIX Century (To the 110th Anniversary of His Death) - Sztejnberg, Aleksander (Substantia, 2021)
Albert Ladenburg (1842-1911) was an outstanding German chemist and historian of chemistry of the second half of the 19th century. He ascertained the formula of ozone as O3 and proposed a triangular prism structure for the molecule of benzene. He studied the structure of aromatic hydrocarbons and organic compounds of silicon and tin, and devoted his work to explaining the structure of alkaloids and their synthesis. The purpose of this paper is to familiarize readers with the important events in the life of Ladenburg and his writing and research activities, in particular some of his experimental results, as well as his selected publications.